Stunting merusak masa depan anak: Ibu di Desa Pinang, lindungi mereka - Romi Anugrah; Agussalim; Erika Fitrayani (P3HKI - Universitas Muhammadiyah Parepare, 2021)
Stunting is a chronic malnutrition problem in young children that impacts physical growth and cognitive development. This community service activity aims to improve mothers' knowledge about stunting prevention through education and demonstration activities in Pinang Village. Pregnant and lactating mothers are the primary participants in this activity. The methods used include education and demonstrations of cooking nutritious food. The results of the activity showed an increase in participants' knowledge of balanced nutrition and the factors that cause stunting. In addition, participants are enthusiastic about participating in the activities and show a commitment to applying the knowledge they have gained. However, further efforts are needed to change behavior and ensure long-term change. The potential of local foods such as dangke and moringa leaves can be a solution to address nutritional problems in the village. The challenges faced are the relatively high price of dangke and the lack of public knowledge about the utilization of moringa leaves. Therefore, there needs to be cooperation between various parties to increase production and diversify local food products, as well as provide intensive education to the community.